Design and implementation of biquad digital filter - Pradabpet, C.; Yimman, S.; Hinjit, W.; Chivapreecha, S.; Dejhan, K. (My University, 2003)
This paper presents a design and implementation of biquad digital filter based on poles-zeros placement on a unit circle of z-plane. The proposed digital filter can be given three frequency-responses as lowpass filter (LPF), highpass filter (HPF) and bandpass filter (BPF) at the same time. In the design process the Matlab program was used, for real world implementation by using TMS320C31 DSP board. The experimental results shown by the dynamic signal analyzer to indicate that the obtained frequency responses give the same results as design specifications.
Keywords: Active filters; Band pass filters; Communication industry; Cutoff frequency; Digital filters; Digital signal processing; Equations; Filtering theory; Transfer functions; Transforms